PROTOTYPE OF FLOOD EARLY WARNING SYSTEM (EWS) USING TELEGRAM BROADCAST MESSAGE NOTIFICATION - Budi Cahyo Wibowo (Jurnal Media Elektrik, 2024)
Flooding has until now become a serious problem in various regions in Indonesia. Flooding is a problem that occurs due to increasing the volume of excess water in rivers that are influenced by human activities that are not friendly to the environment. Floods have quite a lot of negative impacts, one of which is the damage to community facilities and infrastructure. Community preparedness is needed to reduce the negative impact of the flood. One solution that can be done is to design a flood Early Warning System (EWS) as a tool in detecting water levels before the arrival of flood hazards. Mitigation activities need to be complemented by a monitoring system based on the environmental conditions of the surrounding community. This research aims to make a prototype of a flood early warning system that is easy to operate and effective to detect the arrival of floods. In the prototype there is a level switch sensor that can detect high movements of water levels in the watershed. High level information on the water level is then sent periodically in the form of notifications via telegram to the smartphones of community residents whose numbers are registered in the system. From the test results, the ultrasonic sensor obtained 98.7% read accuracy results and a delay time in sending telegram notifications of 3-5 seconds.